Optimised Photocatalytic Degradation of Crystal Violet Over 1wt% MgO-ZnO Composite Catalyst - Gaya, Umar; Abdul-Aziz Umar, Sa'adatu (Journal of Science and Technology, 2019)
Crystal violet is a member of toxic, environmentally ubiquitous basic dyes that must be eliminated. In this paper, the performance of 1wt % MgO-ZnO suspensions in the photocatalytic degradation of this dye is reported. The catalyst was characterized by x-ray diffraction (XRD) and scanning electron microscopy (SEM). The degradation and mineralization of crystal violet were monitored UV-Visible spectrophotometer and total organic carbon analyzer. The XRD analysis of the catalyst revealed a hexagonal wurtzite structure. The effect of operating variables such as initial crystal violet concentration, catalyst concentration and pH of the solution was optimized using the Box-Behnken design and response surface methodology. The degradation model was statistically remarkable with p<0.0001%. The maximum degradation efficiency of prepared catalyst was found to be 95 %. The degradation kinetics agreed with the Langmuir-Hinshelwood model. However, only 60% of total crystal violet-based organic carbon was removed from the solution due to recalcitrance of this environmentally important compound.